A virtual reality computing platform for real time 3D visualization - Alvarado, Yoselie (2012)
In the last decade, virtual reality (VR) systems have been used to enhance the visualization of design projects. The VR techniques allow to the designer interacting and modelling in a more intuitive and e cient way. Current 3D and animated simulation tools are a new chal- lenge for 3D visualization. In this paper we propose a general VR com- puting platform that enables real time visualization of 3D scenarios for manufacturing and forensic simulations. The platform is able to treat static and dynamic 3D environments, allowing to share the experience of navigation in the scene among the users, even geographically distributed. The platform proposed is validated through a case study using real time 3D models manipulations and interaction in a simulated car crash.